Strategi Guru Dalam Menerapkan Pembelajaran Berdiferensiasi Pada Kurikulum Merdeka Pada Siswa Kelas IV Fase B - Titi Rahayu; Firman Firman; Hisbullah Hisbullah (Institut Agama Islam Hidayatullah Batam, 2025)
This study analyzes teachers' strategies for implementing differentiated learning within the Independent Curriculum for fourth-grade students in Phase B at SDN 24 Temalebba Palopo. Using a descriptive qualitative method, data were collected through observations, interviews, and documentation from fourth-grade teachers. The results indicate that the Independent Curriculum has been implemented at SDN 24 Temalebba, particularly in the fourth grade, which adopted it earlier than other grades. The main strategy involves mapping students' learning needs through diagnostic assessments to identify their interests and readiness before the learning process. The implementation of differentiated learning at SDN 24 Temalebba is also influenced by supporting and inhibiting factors, which encompass both internal and external aspects from students and teachers.